Nursing actions and syphilis in people deprived of liberty: integrative review (Research, Society and Development, 2020)
Introduction: syphilis is a sexually transmitted infection, with a significant worldwide incidence. People deprived of their liberty have a high chance of acquiring it based on their sociodemographic characteristics and the conditions of Brazilian prisons. This indicates the relevance of this study, designed as the objective of understanding the potential of nursing actions to control syphilis in this population. Methodology: integrative review carried out on the databases: Spanish Bibliographic Index in Health Sciences, Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online and Scientific Electronic Library Online, with the descriptors syphilis and prisoners, with the Boolean term and, according to the PRISMA protocol, a corpus of 11 articles was obtained. Results: health counseling and screening are the main actions to control syphilis in the prison system. The first performed by health professionals and the second by nursing. Both are performed to identify the bacteria and to guide the use of condoms. Conclusion: nursing actions to control syphilis in the prison system seem to be aimed at meeting productivity goals. The allocation of basic units in prison environments is urgent in order to provide health care to this population and reduce expenses with travel and escapes.